Metabarcoding of Parasitic Wasp, Dolichogenidea metesae(Nixon)(Hymenoptera: Braconidae) That Parasitizing Bagworm, Metisa plana Walker (Lepidoptera: Psychidae) - Aqilah Sakinah, Badrulisham; Muhammad Abdul-Latif, Abu Bakar; Badrul-Munir, Md. Zain; Shukor, Md-Nor; Mohd Ridwan, Abd Rahman; Nur Syafika, Mohd Yusof; Madihah, Halim; Salmah, Yaakop (Penerbit Universiti Sains Malaysia, 2022)
Microbiome studies of the parasitoid wasp, Dolichogenidea metesae (Nixon) (Hymenoptera, Braconidae) are important because D. metesae has potential as a biological control agent to suppress the pest, Metisa plana Walker (Lepidoptera, Psychidae). Three field populations of parasitic wasps with different Integrated Pest Management (IPM) practices to control M. plana collected from Perak state (Tapah) and Johor state (Yong Peng and Batu Pahat districts) in Peninsular Malaysia were studied. Bacterial community composition and structure were analysed using α and β diversity metrics. Proteobacteria (83.31%) and Bacteroidetes (6.80%) were the most dominant phyla, whereas unknown family from order Rhizobiales was the most abundant family found in all populations followed by Pseudomonadaceae. Family Micrococcaceae was absent in Tapah. Rhizobiales gen. sp. and Pseudomonas sp. were abundant in all populations. Pearson’s correlation analysis showed the strongest correlation between individuals of Batu Pahat and Yong Peng (r = 0.89827, p < 0.05), followed by Tapah and Yong Peng with r = 0.75358, p < 0.05 and Batu Pahat and Tapah (r = 0.69552, p < 0.05). We hypothesise that low diversity and richness in Tapah might be due to direct and indirect effect of insecticides application. This preliminary data was the first study to do inventory of the microbiomes in the gut of the D. metesae.